Philosopher as a Therapist: Learning from Wittgenstein - Tyler, Peter (Journal of Dharma, 2015)
Recent commentators have suggested that Ludwig Wittgenstein (1889-1951) can be understood as much as a therapist as a logician or theoretician. This paper explores how Wittgenstein ‘goes about his work’ as a therapist by looking at two aspects of his writings: the Übersichtliche Blick or ‘Way of Seeing’ and the move in his philosophy from thinking to seeing to acting. The paper concludes by suggesting that a Wittgensteinian approach to learning could be categorised as a view of pedagogy as ‘astonishment’.